Together against sexual harassment rebranding of the UP Diliman Office of Anti-Sexual Harassment and an educational sexual harassment prevention campaign which aims to teach consent, boundaries, and different forms of sexual harassment to UP Diliman undergraduate students - Espinosa, Ma. Angela Luz L.
Sexual harassment is any sexual action that is unwelcomed or uninvited. It can happen anywhere and the UP Diliman campus is no exception to this. Over the years the cases of sexual harassment handled by the UP Diliman Office of Anti-Sexual Harassment has been increasing. The main perpetrators are male undergraduate students. In order to mitigate this the UP Diliman OASH has created a policy alongside with the Vice-Chancellor in order to require all departments of the UP Diliman community to attend an annual Anti-Sexual Harassment Seminar. Despite this policy, the awareness levels between UP Diliman undergraduate students about these topics still varies from person to person.